Web social science concepts, data and tools for social scientists in the digital age - Ackland, Robert (Sage, 2013)
This book provides readers with a comprehensive guide to the theory and practice of Web Social Science. It demonstrates how the Web is being used to collect social research data, such as online surveys and interviews, as well as digital trace data from social media environments,such as Facebook and Twitter. It also illuminates how the advent of the Web has led to traditional social science concepts and approaches being combined with those from other scientific disciplines, leading to new insights into social, political and economic behavior.